Pengaruh Kepercayaan dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian pada Situs Bukalapak di Lombok Timur - Rahmatullah, Arwin Yafi; Rempala, Adinda Cahaya (PT. PENERBIT TIGA MUTIARA, 2023)
In the era now, the rapid development of technology makes people use the internet. E-commerce players use the internet as a digital marketing medium. One of the e-commerce that developed at that time was Bukalapak. This study aims to determine the effect of trust and ease of use of applications on purchasing decisions on the Bukalapak site in East Lombok. The method used in this research is associative method and the type of data used is quantitative data. The population of this study were all people who used the Bukalapak application in East Lombok. Determination of the sample using Non-Probability Sampling with a total of 75 respondents. The data analysis method uses validity test, reliability test, classical assumption test, hypothesis testing and multiple linear regression. The results of this study indicate that the trust variable has a positive and significant influence on purchasing decisions The Ease-of-Use variable has a positive and significant influence on purchasing decisions.